GW24-e3625 Effects of apelin on the phosphodiesterase 1 expression and oxidative stress levels in mouse kidney fibroblast cells. (1st October 2013) - Zhong, JiuChang; Song, Bei; Zhang, Xiaoxiao; Zhang, Zhenzhou; Oudit, Gavin Y; Yingle, Xu; Gao, Pingjin; Wang, Jiguang
Abstract : Objectives: Apelin is a recently-discovered cardiovascular bioactive polypeptide with multiple biological effects, which is the endogenous ligand of the orphan G protein-coupled receptor-APJ receptor and may cause vasodilation and lower blood pressure levels. This study focused on the effects of Apelin on the phosphodiesterase 1 (PDE1) expression and oxidative stress levels in mouse kidney fibroblast cells. Methods: The mouse kidney fibroblast cells were primary cultured using the routine method. The angiotensin II (Ang II; 100 nmol/L) was used to stimulate the cells for 1 h in the presence and absence of Aplein (100 nmol/L), PDE1 inhibitor vinpocetine (10 μmol/L) and extracellular regulated protein kinase (ERK) inhibitor PD98059 (10 mmol/L). The specific fluorescent probe-dihydropyridinum (DHE) staining and colorimetric method were used for the determination of superoxide generation and malondialdehyde (MDA) content in cells, respectively. Results: In the cultured mouse kidney fibroblast cells, exposure to Ang II (100 nmol/L) obviously promoted protein expressions of PDE1A and PDE1B (n = 5-6; P < 0.01, respectively), without having a differential effect on the expression of PDE1C. These changes were associated with marked increases in phosphorylated expression of ERK1/2, superoxide generation and MDA levels (n = 5-6; P < 0.01, respectively). In addition, treatment with Apelin (100 nmol/L) and PDE1 inhibition with vinpocetine (10 μmol/L) significantly prevented expressions of PDE1A and PDE1B mediated by Ang II in cells (n = 5; P < 0.05, respectively). More importantly, intervention with Apelin (100 nmol/L) and vinpocetine (10 μmol/L) strikingly reduced the cellular oxidative stress in response to Ang II, as evidenced by decreases in MDA levels and superoxide production, linked with a marked downregulation in phosphorylated ERK1/2 levels (n = 5-6; P < 0.05 or P < 0.01, respectively). Conclusions: Treatment withApelin significantly prevents the oxidative stress formation in cultured mouse kidney fibroblast cells in response to Ang II through the modulation of PDE1-ERK1/2 signalling pathway, suggesting the potential anti-oxidative stress effect of Apelin. The enhanced activities and/or expression of Apelin may have potential therapeutic benefits on renal diseases associated with oxidative stress. This work was supported by National Natural Science Foundation of China (81170246 & 30973522) and Shanghai Pujiang Talents Program (11PJ1408300).